Instrument Validation of Students’ Analytical Thinking Skills in the Natural Science Learning by Using the Rasch Model - Suyatman Suyatman (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
The aim of this study is to validate the analytical thinking skills test instrument using the Rasch Model. The method uses quantitative research methods The essay test was used to evaluate the 85 students attending the PGMI IAIN Surakarta Study Program in Indonesia. Data analysis used the Rasch model–quest application because this model is known for its use in the item response theory. The essay test used to measure student analytical thinking skills in the natural science class was found to be valid, with an adequate level of difficulty, and most of the questions were within the range of student abilities. This study found a prototype instrument for analytical thinking skills in natural science learning through the analysis of the Rasch Model. This instrument can be used to help students measure their ability to think critically and analytically. The results can be used as a reference for instructors and researchers in designing, producing, and analyzing instruments for teaching students' analytical thinking skills in natural science learning.